Kreativitas Penggunaan Media Dampak Covid-19 UMKM Krepek Ikan Belut Di Desa Branta Tinggi Kecamatan Tlanakan Kabupaten Pamekasan - Kusyairi Kusyairi; M. Khoiri; Sabrina Sapitri (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Micro, Small and Medium Enterprises (MSME) sector is one of the sectors most affected by the COVID-19 pandemic. The purpose of this community service activity is to increase understanding, skills and value added marketing of Micro, Small and Medium Enterprises (UMKM) Eel Crackers products affected by the Covid19 pandemic. We try to be a motivator and facilitator for residents, especially in rural areas. The village of Branta Tinggi is located around the coast and adjacent to the sea which makes the livelihoods of most of the people as fishermen, farmers, ranchers. the condition of natural resources is abundant, it's just that residents are less familiar with applied knowledge and technology in education, economy, agriculture and animal husbandry. The method used in this community service activity is counseling and business assistance in the textile sector. The result of this community service activity is an understanding and an increase in the income earned by partners.